Pulmonry function test in spinning and weaving workers in Iraq - Hashim, Hashim Mahdi; Dawood, Haider Noori; Al Hamadani, Lens Faiq (AL-Kindy College Medical Journal, 2014)
Background :The cotton factories have difference steps, spinning and weaving are van important parts of the factories. Cotton industry workers are exposed to various hazards in the different departments of textile factories. The major health problems associated with cotton dust are respiratory problems. Cotton workers display an excess of lung function abnormalities when compared to a community control population.Aim of Study: This study assessed the effect of exposure to cotton dust in spinning and weaving workers on the lung function in Iraq, by measuring Forced Vital Capacity (FVC),Forced Expiratory Volume in the first second(FEV1), FEV1 ∕ FVC Ratio, and Forced Expiratory Flow 50%(FEF50%),with varying degree of reduction in lung function.Methods:151 workers exposed to cotton dust were enrolled in the study, and 100 non exposed workers were selected as control. The age of the workers ranged between 20 to 60 years. Both groups were smokers and non smokers, has no chronic pulmonary disease or symptoms during the time of the study. Sprometric study was used for measuring the lung function.Results: Statistically significant reduction in FEV1and FEF50%were found in exposed workers when compared to control. Lung function indices were not affected with increasing duration of exposure to cotton dust nor to smoking.Conclusion: Exposure to cotton dust in spinning and weaving workers may result in reduction in the pulmonary function and may lead to respiratory diseases. So improvement in protective measures is recommended.